Absence of topology in Gaussian mixed states of bosons - Mink, Christopher D.; Fleischhauer, Michael; Unanyan, Razmik (Physical Review B, 2019)
In a recent paper [Bardyn, Phys. Rev. X 8, 011035 (2018)2160-330810.1103/PhysRevX.8.011035], it was shown that the generalization of many-body polarization to mixed states can be used to construct a topological invariant that is also applicable to finite-temperature and nonequilibrium Gaussian states of lattice fermions. The many-body polarization defines an ensemble geometric phase that is identical to the Zak phase of a fictitious Hamiltonian, whose symmetries determine the topological classification. Here we show that in the case of Gaussian states of bosons, the corresponding topological invariant is always trivial. This also applies to finite-temperature states of bosons in lattices with a topologically nontrivial band structure. As a consequence, there is no quantized topological charge pumping for translationally invariant bulk states of noninteracting bosons.
CRIS-Team Scopus Importer:2023-03-27